2010
DOI: 10.3109/10837451003739297
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable poly(D, L-lactide-co-glycolide) (PLGA) microspheres for sustained release of risperidone: Zero-order release formulation

Abstract: The preparation and investigation of sustained-release risperidone-encapsulated microspheres using erodible poly(D, L-lactide-co-glycolide) (PLGA) of lower molecular weight were performed and compared to that of commercial Risperdal Consta™ for the treatment of schizophrenia. The research included screening and optimizing of suitable commercial polymers of lower molecular weight PLGA50/50 or the blends of these PLGA polymers to prepare microspheres with zero-order release kinetics properties. Solvent evaporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In a previous study, poly(ε-caprolactone)/poly(propylene glutarate) (PCL/PPGlu) copolymer blends were evaluated as proper controlled release carriers for the preparation of risperidone transdermal patch formulations, with results showing that the synthesis and preparation of novel aliphatic polyester-based patches were able to optimize the drug dissolution profile [ 15 ]. Additionally, several other studies have attempted to overcome the marketed risperidone depot drawbacks, such as the development of a 3-month drug releasing risperidone formulation using polycaprolactones [ 26 ], or the reduction of drug’s release lag-period by either altering the microsphere’s preparation process [ 27 , 28 ], or by incorporating suitable bases (organic or inorganic) in PLGA based microspheres [ 29 ]. Therefore, it was the aim of the present study to evaluate, for the first time, the preparation of risperidone controlled release depot formulations based on novel polymer mixtures of PLA and poly(propylene adipate) (PPAd).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, poly(ε-caprolactone)/poly(propylene glutarate) (PCL/PPGlu) copolymer blends were evaluated as proper controlled release carriers for the preparation of risperidone transdermal patch formulations, with results showing that the synthesis and preparation of novel aliphatic polyester-based patches were able to optimize the drug dissolution profile [ 15 ]. Additionally, several other studies have attempted to overcome the marketed risperidone depot drawbacks, such as the development of a 3-month drug releasing risperidone formulation using polycaprolactones [ 26 ], or the reduction of drug’s release lag-period by either altering the microsphere’s preparation process [ 27 , 28 ], or by incorporating suitable bases (organic or inorganic) in PLGA based microspheres [ 29 ]. Therefore, it was the aim of the present study to evaluate, for the first time, the preparation of risperidone controlled release depot formulations based on novel polymer mixtures of PLA and poly(propylene adipate) (PPAd).…”
Section: Introductionmentioning
confidence: 99%
“…Su et al ., has developed a PLGA based risperidone microspheres without a lag period and tested it successfully in a rat model. [ 9 ] Further, the microspheres released the drug according to a zero-order release profile. D’Souza et al ., have developed novel risperidone microspheres and successfully avoided co-administration of oral tablets.…”
Section: Discussionmentioning
confidence: 99%
“…To address this problem research groups have developed similar formulations with other PLGAs. [ 7 8 9 ] Although the results from their studies led to formulations which avoided oral supplementation and demonstrated zero-order drug release, the in vivo drug release was sustained for only up to 45 days. However, a 3 month drug-releasing microsphere formulation can be prepared using PCLs.…”
mentioning
confidence: 99%
“…The most commonly used polymer is poly (lactideco-glycolide) (PLGA), which has been approved by US Food and Drug Administration (FDA). Note that its molecular weight and mole ratio of monomers can directly affect the drug release behaviors of microspheres (Janoria and Mitra, 2007;Su et al, 2011). The mainly prepared methods of microspheres are the emulsion solvent evaporation, spray drying and phase separation (Cleland, 1998;Giunchedi et al, 2000;Liu et al, 2010;Ramazani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, galantamine pamoate (GLT-PM) was synthesized and loaded on the PLGA microspheres, which were prepared using an oil/water emulsion solvent evaporation method. To achieve the aimed release period of 2-4 weeks of microspheres, the molecular weight of PLGA and its mole ratio of monomers were 15 kDa and 75:25, respectively (Janoria and Mitra, 2007;Su et al, 2011). Plackett-Burman design (PBD) was applied for the optimization of formulation and process parameters.…”
Section: Introductionmentioning
confidence: 99%